2015
DOI: 10.1111/ppe.12203
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Adipokines and Birth Outcomes

Abstract: Background Adipokines can serve as a measure of adipose tissue activity. Although birthweight correlates with neonatal adiposity, findings for cord blood levels of adipokines and birth outcomes have been conflicted. Therefore, we determined the cross-sectional associations between adipokines measured in newborn dried blood spots (DBS) and birth outcomes. Methods The Upstate KIDS study enrolled mothers and infants from 2008 to 2010. Among infants whose parents consented to use of residual DBS from Newborn Scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 36 publications
5
33
0
Order By: Relevance
“…Mean cord adiponectin levels were significantly different across groups defined by gestational age at birth, with early preterm children (8.29 μg/mL) having the lowest levels, followed by late preterm (11.51 μg/mL) and term infants (16.90 μg/mL) (p value <0.001). Consistent with other studies (Lenz and Diamond 2012; Mantzoros et al 2009; Nakano et al 2013; Yeung et al 2015; Martos-Moreno et al 2009; Hellgren et al 2015), we observed that cord adiponectin was associated with the duration of gestation (Online Resource Table 1). Figure 1 shows the distribution of cord adiponectin by preterm status.…”
Section: Resultssupporting
confidence: 92%
“…Mean cord adiponectin levels were significantly different across groups defined by gestational age at birth, with early preterm children (8.29 μg/mL) having the lowest levels, followed by late preterm (11.51 μg/mL) and term infants (16.90 μg/mL) (p value <0.001). Consistent with other studies (Lenz and Diamond 2012; Mantzoros et al 2009; Nakano et al 2013; Yeung et al 2015; Martos-Moreno et al 2009; Hellgren et al 2015), we observed that cord adiponectin was associated with the duration of gestation (Online Resource Table 1). Figure 1 shows the distribution of cord adiponectin by preterm status.…”
Section: Resultssupporting
confidence: 92%
“…In the same way as lactoferrin does, resistin decreases progressively in maternal milk . Resistin is a metabolic hormone that plays important roles in regulating energy homeostasis and carbohydrate/lipid metabolism, is mainly secreted by adipocytes, impairs glucose homeostasis, and opposes the action of insulin in peripheral tissues . On the other hand, pro‐inflammatory cytokines IL‐1β, TNF‐α, and IL‐6 stimulate the production of resistin .…”
Section: Discussionmentioning
confidence: 99%
“…NDBS were stored at 4°C and later retrieved for blood spot analyses. Punches of the residual spots were extracted and handled in a similar manner as previously described . Briefly, blood spots were extracted overnight (18‐20 hours) at 4°C with 60 μL of elution buffer in low‐binding 96‐well round bottom plates (catalogue #1830‐9600, USA Scientific, Ocala, FL) on an orbital shaker (Titer Plate Shaker, model # 1830‐9600, USA Scientific, Ocala, FL) at 500 ± 50 rpm.…”
Section: Methodsmentioning
confidence: 99%